Growing up gay and religious. Conflict, dialogue, and religious identity strategies - Ganzevoort, R.R. (Mental health, religion & culture, 2011)
Homosexuality has become a divisive issue in many religious communities. Partly because of that, individuals growing up in such a community and experiencing same sex attractions need to negotiate the messages about homosexuality with their own experiences. This paper explores the identity strategies of religious communities as the background of individual identity struggles. Following a discussion of Bauman's grammars of identity/alterity, it describes four different discourses employed in conservative protestant and evangelical circles: holiness, subjectivity, obedience, and responsibility and four modes of negotiation: Christian lifestyle, gay lifestyle, commuting (compartmentalisation), and integration. By combining an analysis of discourses on the community level with individual strategies, this narrative research helps to better understand the interactions of (group) culture and individual coping.